Undergraduate medical education amidst volatility, uncertainty, complexity, ambiguity - Camarata, Troy; Spizzieri, Angelina; Kulkarni, Anand (Frontiers in Medicine, 2025)
Undergraduate medical education, especially in the United States, is being shaped by an environment that is changing at an unprecedented pace, creating new challenges for institutions, faculty, and students. For medical education to adapt to the changing environment, influencing factors must be identified and categorized, allowing for the development of strategies that work within the new landscape. Volatility, uncertainty, complexity, and ambiguity (VUCA) is a method to analyze the factors driving change. Here, we apply the VUCA framework to undergraduate medical education, highlighting key influencing factors including artificial intelligence, decentralized approaches to learning, expansion of medical schools, and new demands on faculty and students. The goal is to identify how these influences are impacting medical education allowing for creative and innovative strategies to be employed that mitigate disruptive forces and take advantage of new opportunities to the benefit all stakeholders.